Numerical Simulation of Tritium Diffusion Behavior in FeCrAl Cladding - Yin, Chunyu; Liu, Rong; Jiao, Yongjun; Liu, Shengyu; Duan, Zhengang; Gao, Shixin; He, Liang; Chen, Ping (Frontiers in Energy Research, 2022)
In this article, a simulation code for tritium diffusion behavior analysis in FeCrAl cladding is developed based on the COMSOL platform. The simulated results are in good agreement with experimental and theoretical results. The effects of different concentrations of tritium and temperature distributions on the diffusion behavior of tritium in FeCrAl cladding were further investigated. Finally, the optimal effect of different coating schemes on the tritium resistance of the FeCrAl cladding was investigated. The results show that higher temperatures lead to higher cladding diffusion coefficients, which will further lead to higher fluxes of tritium into and out of the cladding, which is found to further result in a higher tritium flux into and out of the cladding, as well as shorter tritium diffusion times. It is found that higher temperature will lead to more tritium flux into and out of the cladding and shorter time for the tritium flux to reach a steady state on the right side of the cladding. At the same time, the higher tritium partial pressure on the fuel side of the cladding will lead to a longer time for the tritium flux to reach a steady state on the water side of the cladding. The longer time to reach the steady state on the water side of the cladding increases the tritium flux into the cladding.